Evaluasi dan Perbaikan UI/UX Pada Aplikasi Bujang Kurir Dengan Menggunakan Metode Design Thinking - Nurul Islamiah Wulandari (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
Bujang Kurir is a mobile application providing delivery services with a personal delivery concept and emphasizing collaboration with UMKM, home industries, and other business partners. From initial observations, several issues were identified, such as the inability to track couriers by users, the lack of delivery time estimates, and more. This research aims to identify user experience issues found in the Bujang Kurir app and design improvement recommendations (high fidelity prototype) to address these issues. The methodology used in this research is design thinking, which focuses on the user. This method consists of five stages: empathize, define, ideate, prototype, and test. The participants in this study included 20 people, consisting of both new and existing users of the Bujang Kurir app. In the empathize stage, this research gathered data using usability testing through performance measurement (effectiveness and efficiency aspects), think aloud, SUS questionnaires (satisfaction aspect), and interviews. This process resulted in 39 pain points, which were then converted into 21 improvement recommendations. The study showed a 21.25% improvement in effectiveness, an increase in efficiency of 0.002 goals/sec, and an increase in satisfaction, with the design recommendation prototype receiving a SUS score of  90, categorized as acceptable with an A grade.